Frequency selectivity measured both psychophysically and physiologically - Wells, Tobias T. (2014)
The ability to resolve the individual frequency components of a complex sound is known as frequency selectivity. The auditory system seems to act as a series of overlapping band-pass filters or auditory filters (AF), the width of which describe frequency selectivity. It is a fundamental and extensively studied property of the auditory system, yet its neural basis is not fully understood. This is due, in part, to the fact that two distinct approaches are taken to explore it; psychophysics and physiology, the results of which are difficult to reconcile. AF are measured in quite different ways in the two sub-fields.